2021
DOI: 10.1002/adhm.202100196
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Carbon Dots for Promoting Periodontal Bone Regeneration via Activation of ERK/AMPK Pathway

Abstract: The osteogenic potential of mesenchymal stem cells (MSCs) is severely impaired under persistent inflammation of periodontitis. A highly efficient way to promote or rescue osteogenic potential of MSCs under inflammation remains an unmet goal. Herein, metformin carbon dots (MCDs) with excellent biocompatibility are prepared from metformin hydrochloride and citric acid via a hydrothermal method. The MCDs can more effectively enhance the alkaline phosphatase (ALP) activity, calcium deposition nodules formation, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 74 publications
0
27
1
Order By: Relevance
“…Previous studies showed that metformin had a potentially positive effect on 20% reductions of fracture risk in T2DM patients [ 115 ]. In addition, metformin is indirectly involved in the action of ERK activation and the induction of inducible nitric oxide synthase (iNOS), both of which are an important regulative factor in osteogenesis [ 68 ]. Since metformin has no substantial effect or side effect on the control of glucose levels in nondiabetic individuals, it may be regarded as a potential adjuvant therapeutic drug for bone disorders in patients without diabetes.…”
Section: Discussion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that metformin had a potentially positive effect on 20% reductions of fracture risk in T2DM patients [ 115 ]. In addition, metformin is indirectly involved in the action of ERK activation and the induction of inducible nitric oxide synthase (iNOS), both of which are an important regulative factor in osteogenesis [ 68 ]. Since metformin has no substantial effect or side effect on the control of glucose levels in nondiabetic individuals, it may be regarded as a potential adjuvant therapeutic drug for bone disorders in patients without diabetes.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…It is well known that the osteogenic potential of mesenchymal stem cells (MSCs) is seriously affected by persistent inflammation of periodontitis. Metformin carbon dots (MCDs) including citric acid and metformin hydrochloride effectively improved the activity of ALP, the formation of calcium deposition nodules, the expression of genes and osteogenic proteins in mesenchymal stem cells of the rat bone marrow (rBMSCs), thereafter effectively helped to regenerate lost alveolar bone in periodontitis rats [ 68 ]. A recent study showed that polycaprolactone/chitosan nanofibrous membranes containing metformin would be favored for bone regeneration as guided bone regeneration membranes because it was more suitable for cell proliferation, adhesion, and osteogenic differentiation of rBMSCs [ 69 ].…”
Section: Effects Of Metformin On Cells In Vitromentioning
confidence: 99%
“…The preparation of CDs is very simple and economically undemanding. CDs coated with metformin activated the ERK/AMPK pathway and promoted periodontal bone regeneration [206]. CDs significantly enhanced matrix mineralization, promoted osteogenic differentiation in vitro, and stimulated new bone growth in the skull defect model in vivo [207].…”
Section: Carbon Nanoparticlesmentioning
confidence: 98%
“…Min-Ji Ahn and Goang-Won Cho indicated, in a research conducted in 2017, that activation of AMPK by metformin could have a stimulatory role in human bone marrow mesenchymal stem cells towards neural differentiation (Ahn and Cho 2017 ). Various studies have shown that treatment with metformin is effective in bone structure, including osteoarthritis (Feng et al 2020 ; Li et al 2020a , b ; Li et al 2020a , b ), osteoporosis (Blümel et al 2020 , Guo et al 2022 , Song et al 2022 ), bone regeneration (Ren et al 2021 ; Fang et al 2022 ; Sun et al 2022 ) and osteosarcoma (Paiva-Oliveira et al 2018 ; Zhao et al 2019 , Lu et al 2021 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%